Effect of Mocaf Flour and Tiwai Onion Formulation on Fiber, Antioxidant Activity, and Organoleptic Properties of Onion Sticks - Annas Nabillah, Kholifah; Pangestu Utami, Riana; Susanti, Elvi (Journal of Nutrition and Public Health, 2025)
Background:Diabetes mellitus is a degenerative disease with a high prevalence in Indonesia. Efforts to control blood glucose levels can be achieved by consuming foods with a low glycemic index, high fiber, and rich in antioxidants. Mocaf flour has a lower glycemic index and higher fiber content than wheat flour, while Tiwai onions are rich in flavonoids and phenolic compounds, which act as natural antioxidants. Aims:This study aims to determine the effect of mocaf flour and tiwai onion formulation on fiber content, antioxidant activity, and organoleptic characteristics of onion sticks, as well as to determine the best formula. Methods:This study used an experimental design with a Completely Randomized Design (CRD) of three treatments and three replications. The treatment formulations were F1 (48 g mocaf : 15 g tiwai onion), F2 (42 g mocaf : 21 g tiwai onion), and F3 (36 g mocaf : 27 g tiwai onion). Fiber content analysis was carried out using the gravimetric enzymatic method, antioxidant activity using the DPPH method, and organoleptic tests were carried out on 30 untrained panelists using a hedonic scale. Data were analyzed using ANOVA and further tests were carried out if there were significant differences. Result:The results showed that the formulation affected fiber content, antioxidant activity, and organoleptic properties. Formulation F1 produced the highest fiber content (2.28%) and the best acceptability in terms of taste and texture. Formulation F3 had the highest antioxidant activity (190.13 µg/ml) and the most preferred color by panelists. This indicates that increasing the mocaf composition increases fiber content, while the addition of tiwai onions strengthens antioxidant activity. Conclusion:The combination of mocaf flour and Tiwai onions has the potential to produce onion sticks, a healthy, functional snack that consumers will love. This product can be used as a local food alternative to support diet management for people with diabetes mellitus and to strengthen the use of local food ingredients in nutrition and dietetics innovations.